The Stability of Individual Well-Being in Short Windows of Time: Women’s Perceptions across the Ovulatory Cycle - Villani, Daniela; Iannello, Paola; Cipresso, Pietro; Antonietti, Alessandro (Frontiers in Psychology, 2017)
Empirical research on well-being has rapidly increased in recent years. One of the most dominant issue concerns the degree of cross-situational consistency and stability of well-being across time and this is of particular relevance to women life. The aim of this study was to verify the stability of women well-being in short windows of time specifically across menstrual cycle phases. A within-subject design with 25 normally cycling women (range: 19-26 years) was carried out. The multidimensional assessment of well-being included the administration of psychological well-being, self-esteem, and emotional self-efficacy beliefs questionnaires during both high and low-fertility phases. The results showed the stability of the level of individual well-being across menstrual cycle phases. Albeit preliminary, results indicated that women representations of their well-being do not change according to menstrual cycle. Rather, an effective organization and integration of the entire self-system appears sustained by the stability of well-being measured through a multi-componential assessment over short periods of time.